Osteology of a perinatal aristonectine (Plesiosauria; Elasmosauridae) - O'gorman, José P. (2016)
Fil: O'gorman, José P. Consejo Nacional de Investigaciones Científicas y Técnicas. Buenos Aires, Argentina.